Inter- and Intra-Molecular Organocatalysis of SN2 Fluorination by Crown Ether: Kinetics and Quantum Chemical Analysis - Young-Ho Oh; Wonhyuck Yun; Chul-Hee Kim; Sung-Woo Jang; Sung-Sik Lee; Sungyul Lee; Dong-Wook Kim (Molecules, 2021)
We present the intra- and inter-molecular organocatalysis of SN2 fluorination using CsF by crown ether to estimate the efficacy of the promoter and to elucidate the reaction mechanism. The yields of intramolecular SN2 fluorination of the veratrole substrates are measured to be very small (<1% in 12 h) in the absence of crown ether promoters, whereas the SN2 fluorination of the substrate possessing a crown ether unit proceeds to near completion (~99%) in 12 h. We also studied the efficacy of intermolecular rate acceleration by an independent promoter 18-crown-6 for comparison. We find that the fluorinating yield of a veratrole substrate (leaving group = −OMs) in the presence of 18-crown-6 follows the almost identical kinetic course as that of intramolecular SN2 fluorination, indicating the mechanistic similarity of intra- and inter-molecular organocatalysis of the crown ether for SN2 fluorination. The calculated relative Gibbs free energies of activation for these reactions, in which the crown ether units act as Lewis base promoters for SN2 fluorination, are in excellent agreement with the experimentally measured yields of fluorination. The role of the metal salt CsF is briefly discussed in terms of whether it reacts as a contact ion pair or as a “free” nucleophile F−.